Effects of substituting ytterbium for scandium on corrosion behaviour of Al–Sc alloy. Issue 12 (14th July 2015) - Tuan, N. Q.; Alves, A. C.; Toptan, F.; Lopes, A. B.; Pinto, A. M. P.
Abstract : The localized corrosion and electrochemical behaviour of Al–0.28 wt.% Sc and Al–0.24 wt.% Sc–0.07 wt.% Yb alloys have been studied in 3.5 wt.% NaCl solution. The results showed that the impurity intermetallic phases containing Fe can act as cathodes and promote localized corrosion in the surrounding matrix. Yb had strong effect on the polarization behaviour in the anodic domain of Al–Sc alloy by improving the pitting corrosion resistance of this alloy. It has been deduced that a high number density of fully coherent nano‐sized Al3 Sc or Al3 (Sc, Yb) precipitates in heat treated alloys can enhance the passivation tendency of these alloys.